2023
DOI: 10.1039/d3cc01415k
|View full text |Cite
|
Sign up to set email alerts
|

Single-atomic Fe sites decorated N-doped carbon toward oxygen reduction in MFCs

Abstract: The atomically dispersed Fe-N-C catalyst has been synthesized and enables high power out performance in microbial fuel cells (MFCs). The influence of Fe doping on the electronic properties of N-doped...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Similarly, single atom Fe sites in the N-C showed a higher MFC performance of 3,323 mW m -2 than that of the Pt/C catalyst. The higher performance was due to the optimized Fe-N-C with porous structure and efficient electron transfer properties of the catalyst (Zhao et al, 2023). Long et al reported CoFe-LDH on partially reduced GO (p-rGO) showed 30 times higher MFC performance than the blank due to more the active sites, structural and interlayer diffusion properties of the catalyst (Long et al, 2023).…”
Section: Figurementioning
confidence: 99%
“…Similarly, single atom Fe sites in the N-C showed a higher MFC performance of 3,323 mW m -2 than that of the Pt/C catalyst. The higher performance was due to the optimized Fe-N-C with porous structure and efficient electron transfer properties of the catalyst (Zhao et al, 2023). Long et al reported CoFe-LDH on partially reduced GO (p-rGO) showed 30 times higher MFC performance than the blank due to more the active sites, structural and interlayer diffusion properties of the catalyst (Long et al, 2023).…”
Section: Figurementioning
confidence: 99%
“…6–9 Alternatively, the Fe and N co-doped carbon (FeNC) materials have manifested impressive catalytic activity to replace the Pt catalysts. 10–15 Despite the tremendous advancement in the catalytic activity of FeNC catalysts after delicate modification, the poor stability largely restricts the application of the FeNC catalysts. The proton exchange membrane fuel cells based on the FeNC catalysts suffer from severe stability issues, especially in the first few hours during operation.…”
mentioning
confidence: 99%